Educational training to improve opioid overdose response among health center staff: a quality improvement initiative - Audrey Stephenson; Alessandra Calvo-Friedman; Lisa Altshuler; Sondra Zabar; Kathleen Hanley (Harm Reduction Journal, 2023)
Abstract Background There were seven opioid overdoses in this New York City (NYC) federally qualified health center from December 2018 through February 2019, reflecting the rising rate of overdose deaths in NYC overall at the time. In response to these overdoses, we sought to increase the readiness of health center staff to recognize and respond to opioid overdoses and decrease stigmatizing attitudes around opioid use disorder (OUD). Methods An hour-long training focusing on opioid overdose response was administered to clinical and non-clinical staff of all levels at the health center. This training included didactic education on topics such as the overdose epidemic, stigma around OUD, and opioid overdose response, as well as discussion. A structured assessment was administered immediately before and following the training to evaluate change in knowledge and attitudes. Additionally, participants completed a feedback survey immediately after the training to assess acceptability. Paired t-tests and analysis of variance tests were used to assess changes in pre- and post-test scores. Results Over 76% of the health center staff participated in the training (N = 310). There were large and significant increases in mean knowledge and attitudinal scores from pre- to post-test (p < .001 and p < .001, respectively). While there was no significant effect of profession on attitudinal change scores, profession did have a significant effect on knowledge change scores, with administrative staff, non-clinical support staff, other healthcare staff, and therapists learning significantly more than providers (p < .001). The training had high acceptability among participants from diverse departments and levels. Conclusions An interactive educational training increased staff’s knowledge and readiness to respond to an overdose as well as improved attitudes toward individuals living with OUD. Trial registration: This project was undertaken as a quality improvement initiative at the health center and as such was not formally supervised by the Institutional Review Board per their policies. Further, per the guidelines of the International Committee of Medical Journal Editors, registration is not necessary for clinical trials whose sole purpose is to assess an intervention’s effect on providers.